How environmental regulations and corporate social responsibility affect the firm innovation with the moderating role of Chief executive officer CEO power and ownership concentration - Javeed, Sohail Ahmad; Latief, Rashid; Jiang, Tao; Ong, Tze San; Tang, Yongjun (Elsevier, 2021)
At present, many economies are suffering from environmental problems that have significant effects on the climate and life of human beings, thus, the governments and institutions work to reduce the industrial negative effects on the environment. Based on the Porter Hypothesis, agency theory, and management and organization theory, this study examines the connection between environmental regulations, corporate social responsibility and firm innovation with the moderating role of CEO power and ownership concentration. Importantly, this study divided CEOs into male and female CEO. This study classifies firm innovation into two kinds, such as firm input innovation and firm output innovation. This study selects the sample of Pakistani manufacturing firms and uses the panel data for the period 2008 to 2018. For the analysis purpose, this study employs ordinary least squares (OLS), fixed-effect (FE) model, generalized method of moments (GMM). For more robust results, this study employs the feasible generalized least square (FGLS) model. Based on the findings from the empirical analysis, this study concludes that environmental regulations and corporate social responsibility have a positive relationship with firm innovation (Input and Output). Moreover, a powerful CEO and ownership concentration are valuable for firm innovation (Input and Output), because these factors are positively connected with firm innovation (Input and Output). Majorly, this study contends that environmental regulations and corporate social responsibility are positively connected with firm innovation (Input and Output) because of the interactive role of CEO power. This study supported the role of both male and female CEOs for firm innovative practices. Therefore, firms of developing economies should also consider the female CEO. Besides, environmental regulations and corporate social responsibility also positively connected with firm innovation (Input and Output) because of the interactive role of ownership concentration. Moreover, this study offers various policy implications for governments and policymakers.